Adoption Climate Change on Marketing Strategy : Green Product decision process model - Nuri Purwanto; Erminati Pancaningrum; Rita Murtiani (Proceeding International Conference on Digital Education and Social Science, 2024)
Climate change significantly affects consumer behavior, driving shifts in marketing strategies to accommodate evolving consumer values and expectations, the purpose of this study was to examine the effect of Environmental concerns on green Green purchasing decisions both directly and indirectly through Green willingness to purchase, in this study taking a sample of 100 respondents with the criteria of green cosmetic users who live in Surabaya, data analysis using Structural equation model with smart pls as the analysis tool, from the results it was found that Environmental concerns have a positive and significant effect on green Green purchasing decisions both directly and indirectly through Green willingness to purchase, and Green willingness to purchase has a positive and significant effect on green Green purchasing decisions.